ANALISIS KOMPONEN DAYA TARIK PRODUK WISATA PULAU BERAS BASAH KOTA BONTANG, KALIMANTAN TIMUR - , REZKI KRISDAYANTI SAPUTRI; , Prof. Dr. Marsono, S.U. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Pulau Beras Basah (Beras Basah Island) is a potential area to bring number of tourists. This can be seen from its natural resources as beautiful scenary and the water tourism activities. This study discusses variety of tourism products in Pulau Beras Basah and how the tourist attraction component analysis do to each product. The purpose is to describe and identify the components of each product in Pulau Beras Basah. This studyâs procedures are including: study literature, interviews, direct observation, and questionnaire. This study uses The Tourism Product Theory, Tourist Attraction Theory, and the attraction component analysis. Based on this research, it is known that Pulau Beras Basahâs products have some advantages as easily accessible, panoramic scenary such as the atmosphere in Pelabuhan Tanjung Laut (Tanjung Laut Harbour), the trip from Pelabuhan Tanjung Laut to Pulau Beras Basah, the atmosphere in Pulau Beras Basahâs beach, and the atmosphere of the mainland of Pulau Beras Basah itself. Those atmospheres include the beautiful scenery, marine activities, and its facilities. Based on a result of study involving 45 respondents, it can be stated that the products of Pulau Beras Basah have had is attractive for tourists, but the condition of the facilities available are inadequate. Keywords: Beras Basah Island, tourism product, attraction component